THE RADICAL ISLAMIC ORGANIZATIONS OF CENTRAL ASIA - KARMANOV, Dmitri (CENTRAL ASIA AND THE CAUCASUS, 2004)
Those Islamic political parties using relatively peaceful, non-violent, yet illegal methods to achieve their aims (unsanctioned protest rallies, illegal distribution of printed matter, etc.) are described as radical. Any student of Central Asian political developments should be able to distinguish between Islamic radicalism and Islamic extremism. The latter uses all means, including terrorism and subversion, to push ahead.1 The Ferghana Valley, a densely populated ethnic patchwork, is the center of Central Asian radical Islam. Due to scarce water supplies, appall-ing unemployment, and lack of information the lo-cal people are living on the brink of violent protest under religious slogans.2 An analysis of the available literature and media publications suggests that the radical organizations of the Central Asian Islamic movement greatly vary since 1990 there have been two generations of radical Islamic organizations in the region.